PENGARUH EKSTRAK DAUN SIRSAK (Annona muricata L.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli ATCC 25922 DAN Staphylococcus aureus ATCC 25923 - Nadira .; Siti Raudah; latifah . (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
One of the plants that has long been used as traditional medicine includes soursop leaves (Annona muricata L.). Soursop leaves are commonly used to prevent and treat certain types of diseases caused by bacteria such as diarrhea and skin infections. One of the chemical content of soursop which plays an important role for medicine is flavonoids and tannins. This research was conducted in 5 stages: 1) Making soursop leaf extract, 2) Preliminary test, 3) Phytochemical test, 4) Test sensitivity of soursop leaf extract (Annona muricata L.) on the growth of Escherichia coli bacteria ATCC 25922 and Staphylococcus aureus ATCC 25923 , 5) Observation of inhibitory zones. The second to fourth leaves from the top are used as ingredients. The concentration of soursop leaf extract used is 60%, 70%, 80%, 90%, 100%. Each concentration of extract was tested on media Muller Hilton Agar. The radical zone formed is measured as a barrier to bacterial growth. Analysis of the data used is Simple Linear Regression. The results showed that there was the effect of soursop (Annona muricata L.) leaf extract on the growth of Staphylococcus aureus ATCC 25923 at concentrations of 60%, 70%, 80%, 90% and 100% formed inhibition zones with an average of 11 mm, 11.6 mm, 12.6 mm, 13.6 mm and 14.6 mm. The results showed no effect of soursop (Annona muricata L.) leaf extract on the growth of Escherichia coli bacteria ATCC 25922 at concentrations of 60%, 70%, 80%, 90% and 100% formed inhibition zones with an average of 0 mm, 0 mm , 0 mm, 0 mm and 0 mm. Based on the coefficient value shows T count> T table, or 19,919> 3,182, meaning regression is significant. So the concentration of soursop leaf extract (Annona muricata L.) has a significant effect on the inhibitory zone of Staphylococcus aureus bacteria.